Analytic examination of mechanism for compressive residual stress introduction with low plastic strain using peening - Ryo ISHIBASHI (The Japan Society of Mechanical Engineers, 2016)
Our goal for this study was to understand the cause of the differences in surface properties between surfaces processed using water jet peening (WJP) and shot peening (SP) and to examine the compressive residual stress introduction process with low plastic strain using SP. The dynamic behaviors of stress and strain in surfaces during these processes were analyzed through elasto-plastic calculations using a finite-element method program, and the calculated results were compared with measured results obtained through experiments. Media impacting a surface results in a difference in the hardness and microstructure of the processed surface. During SP, a shot deforms the surface locally with stress concentration in the early stages of the impact, while shock waves deform the surface evenly throughout the wave passage across the surface during WJP. A shot with a larger diameter creates a larger impact area on the surface during shot impact. Thus, SP with a large-diameter shot suppresses the stress concentration under the same kinetic energy condition. As the shot diameter increases, the equivalent plastic strain decreases. On the other hand, the shot is subject to size restriction since the calculated results indicate the compressive residual stress at the surface decreased and occasionally became almost zero as the shot diameter increased. Thus, compressive residual stress introduction with low plastic strain by using SP is considered achievable by using shots with a large diameter and choosing the appropriate peening conditions.